2011
DOI: 10.1149/1.3624606
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cathode Catalyst Layer Structure and Properties Dominating Polymer Electrolyte Fuel Cell Performance

Abstract: Transport of electrons, protons, and oxygen are necessary for the cathode reactions in polymer electrolyte membrane fuel cells, and achieving the optimum structure of the electrode catalyst layer and the efficient transport of reactants is an effective avenue to reduce the use of platinum catalyst. This study applied three-phase boundary and cathode catalyst layer models to understand details of optimally efficient structures for the transport of reaction components. The factors dominating the effects of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 22 publications
2
41
0
Order By: Relevance
“…We found that the oxygen permeation through the ionomer film is a major portion of the total transport resistance through the cathode catalyst layer, especially for low-Pt-loaded catalyst layers. This effect has also been shown in various modeling studies to be a critical issue [17,18]. Therefore, we anticipate that the performance decay might have a similar effect with the oxygen transport resistance.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…We found that the oxygen permeation through the ionomer film is a major portion of the total transport resistance through the cathode catalyst layer, especially for low-Pt-loaded catalyst layers. This effect has also been shown in various modeling studies to be a critical issue [17,18]. Therefore, we anticipate that the performance decay might have a similar effect with the oxygen transport resistance.…”
Section: Introductionsupporting
confidence: 62%
“…One is the calculation result of reducing only A Pt and the other is the calculation result of reducing both A Pt and a eff ion using the relation of Eq. (18). The increase in the proton-transport overpotential is caused by changing the proton-transport distance in the ionomer by shifting the reaction distribution across the cathode CL.…”
Section: Understanding Lossesmentioning
confidence: 99%
“…[13][14][15] Other studies support this contention -that oxygen mass transport resistance through the catalyst layer ionomer plays a large role in determining the power that can be extracted from a fuel cell. 16 It has also been suggested that the total mass transport resistance is exacerbated by a mass transport resistance at the gas/ionomer interface, which becomes increasingly dominant as ionomer film thickness is reduced. [17][18][19] Understanding oxygen mass transport limitations at ionomer | Pt interfaces is therefore of growing interest.…”
Section: -11mentioning
confidence: 99%
“…These decrease the oxygen diffusion resistance in the ionomer and the CL pores. From the previous study (8), the decrease in the oxygen diffusion resistance in the ionomer is considered to be dominant to increase the limiting current density here. On the other hand, in the results with the set (b) (smaller agglomerate size and slower oxygen dissolution rate), the highest limiting current density is achieved with the I/C ratio of 2.0 ( Fig.…”
Section: Effects Of the Agglomerate Size And Oxygen Dissolution Ratementioning
confidence: 99%
“…The simplified agglomerate model (8) was applied as the three-phase boundary model of the cathode CL as shown in Fig. 1(a).…”
Section: Analysis Model and Formulationmentioning
confidence: 99%